TEKNOLOGI PENGOLAHAN AIR MINUM DARI AIR BAKU YANG MENGANDUNG KESADAHAN TINGGI - Widayat, Wahyu (Jurnal Air Indonesia, 2008)
Water is very important need for our live. The lack of water, in term of quqnttity quality would triger serious social & health problems. The requirements for qualified water including element of phisical, chemical & bacteriological. One of chemical parameter in wateris the amount of Ca+2 & Mg+2, namely of hardnes. Since it is harmfull for human health hardness both in industrial and household consumption should be avoided. To cope the problem, there is an exact solution by processing the water with ion exchange filtration. The instalation could be used to process the water from deep well & ordinary well on the lime mountains which generally has a high hardness into qualified drinkable water. Kata Kunci : Air minum, Kapur, Kesadahan, Pengolahan, Penukar ion.